2019
DOI: 10.56899/149.s1.19
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Radiation and In Vitro Induced Banana Bunchy Top Virus (BBTV) Resistant Mutant Lines of Banana cv ‘Lakatan’ (Musa sp., AA)

Abstract: Gamma irradiation coupled with in vitro technology was used to develop BBTV resistance in banana cv ‘Lakatan.’ Ten (10) resistant lines were selected after several generations of evaluation and selection. The selected lines (M1V3–M1V4) showed low disease incidence in the field under high disease pressure and, likewise, low disease incidence with aphid inoculation of the virus. Further disease evaluation (M1V4–M1V5) on these lines consistently showed low BBTV disease incidence (11.62–28.57%) 30 mo from planting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Two banana genotypes, wild Musa balbisiana (BBTV-resistant 9 ) and Musa acuminata ‘Lakatan’ (BBTV-susceptible 6 ), were mock- and BBTV-inoculated by Pentalonia nigronervosa and the RNA samples from young leaf tissues were isolated at 72 h post-inoculation (hpi). In total, 12 RNA samples were sent for next-generation sequencing using Illumina NextSeq 500/550 to represent the total transcriptomic profiles of BBTV-free and BBTV-inoculated resistant and susceptible banana genotypes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two banana genotypes, wild Musa balbisiana (BBTV-resistant 9 ) and Musa acuminata ‘Lakatan’ (BBTV-susceptible 6 ), were mock- and BBTV-inoculated by Pentalonia nigronervosa and the RNA samples from young leaf tissues were isolated at 72 h post-inoculation (hpi). In total, 12 RNA samples were sent for next-generation sequencing using Illumina NextSeq 500/550 to represent the total transcriptomic profiles of BBTV-free and BBTV-inoculated resistant and susceptible banana genotypes.…”
Section: Resultsmentioning
confidence: 99%
“…BBTV-resistant wild M. balbisiana 9 (Acc No. MB 13-155) conserved and maintained at the National Plant Genetic Resource Laboratory (NPGRL), Institute of Plant Breeding, University of the Philippines Los Baños (IPB-UPLB) and BBTV-susceptible M. acuminata ‘Lakatan’ 6 were used for the transcriptomic analysis (Fig. 3 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous mutation work in Musa spp. has focused on improving agronomic character-istics, like plant height [42,43] and yield [5,44,45], and the disease resistance [46,47] of commercially relevant varieties. While these outcomes were not the primary focus of the present study, the phenotypic variation observed in the initial field planting of 631 variants (Phase II) demonstrates the 35 Gy irradiation treatment was effective in generating a population of Goldfinger mutant lines from which such improved agronomic selections could be made.…”
Section: Discussionmentioning
confidence: 99%
“…The virus circulates within the body of the tick but does not replicate within its vector body nor is there any transovarial transmission (Watanabe & Bressan 2013b). To be an infective viral vector, P. nigronervosa must obtain hosts or plants affected by banana stunting virus for at least 4 hours, but most of these leaf ticks must skip the feeding period of up to 18 hours (Damasco et al, 2020). Once the tick has become infective, this vector can maintain its infectiveness for a period of time from 15 -20 days, it can even be up to its entire life (Rahayuniati et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%